The role of trust in mediating the relationship between market orientation and relational satisfaction / Dr. Zainuddin Zakaria … [et al.] - Zakaria, Zainuddin; Abdul Halim, Muhammad Abi Sofian; Mohd Hussain, Siti Hajar; Kamaludin, Mohd Ariff; Muhamad Yusof, Ahmad Tarmizi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2021)
Many organisations are forming partnerships to enhance their capabilities to improve product quality, innovation, and market research (Wong et.al 2005). This paper aims to look into how the concept of trust (Benevolence and Credibility) can mediates the relational satisfaction of private higher learning institutions (HLI) that forms academic franchise with public universities. Data were collected from decision makers chosen from these private HLIS. We discovered that only the perception of Credibility and not Benevolence mediates the relationship between market orientation and the relational satisfaction experienced by the private higher learning institutions. The conceptual model created through the findings of this paper will help managers of both the public and private higher learning institutions to better understand the role of trust in the collaboration of higher learning institutions. Policy makers, decision makers and education authorities will benefit from this model by considering using credibility as an essential component of policies, rules and regulation in the formation of collaboration in the context of higher education.